2023
DOI: 10.13057/biodiv/d240449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Beauveria bassiana and Metarhizium anisopliae on the growth of Spodoptera frugiperda by seed inoculation

Abstract: Abstract. Sari JMP, Herlinda S, Suwandi S, Elfita. 2023. Effect of Beauveria bassiana and Metarhizium anisopliae on the growth of Spodoptera frugiperda by seed inoculation. Biodiversitas 24: 2350-2357. Spodoptera frugiperda J.E.Smith 1797 larvae are more difficult to control because they hide in the leaf sheaths. Therefore, it is necessary to use endophytic entomopathogenic fungi to control S. frugiperda larva. The aim of this research was to observe the effect of endophytic Beauveria bassiana (Bals.-Criv.) Vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The corpse's body can grow and appear as sexual ascospores and asexual conidia (Boomsma et al 2014), and the fungi can induce mycosis (Russo et al 2020). The symptoms of mycosis in the corpse's body in this present study were similar to the symptoms from the previous studies; the corpses became hardened, stiffened, dry, shriveled, and covered with mycelium and spores of fungus Lestari et al 2022;Sari et al 2023).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The corpse's body can grow and appear as sexual ascospores and asexual conidia (Boomsma et al 2014), and the fungi can induce mycosis (Russo et al 2020). The symptoms of mycosis in the corpse's body in this present study were similar to the symptoms from the previous studies; the corpses became hardened, stiffened, dry, shriveled, and covered with mycelium and spores of fungus Lestari et al 2022;Sari et al 2023).…”
Section: Discussionsupporting
confidence: 85%
“…The previous study showed that the larvae began to die 3-4 days after the neonate larvae treated with endophytic B. bassiana and M. anisopliae (Sari et al 2023). The fungal spores cause dead larvae through hyphae of the endophytic fungus to enter orally, and the fungi infect through the intestinal epithelium (Boomsma et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From previous surveys in 2021, we found 20 entomopathogenic fungal isolates isolated from plants that were confirmed to be endophytes [7], and the fungi also had the potential to kill fall armyworm or Spodoptera frugiperda larvae and cause deformed pupae and adults in pest management [8]. Similarly, entomopathogenic fungi isolated from lepidopteran carcasses have been confirmed to be endophytic and capable of killing S. frugiperda larvae and adversely affecting pest development [9,10]. However, whether these endophytic fungi can cause the host plants to grow is not yet known.…”
Section: Introductionmentioning
confidence: 91%